An evaluation of the interior design of selected convenience stores in terms of their compliance with the requirements for accessibility of persons with disabilities - Cendaña, Dianne Feliz D.; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
This multiple case study attempted to evaluate the interior design of selected convenience stores in terms of their compliance to the provisions stipulated in Batas Pambansa Bilang 344 or Accessibility Law. Using purposive sampling, three convenience stores located in Metro Manila were chosen as samples for this study, represented by their respective store managers. The data gathering procedures involved observation of store interiors and interviews with the store managers and/or employees. With the use of an observation guide to evaluate the three convenience stores in terms of their compliance to the Accessibility Law, the results showed that the current interior design of all convenience stores do not entirely comply with the provisions of Batas Pambansa Bilang 344. While the three convenience stores have provided some accessibility features for persons with disabilities (PWDs), the results revealed that there are some interior space requirements for PWDs that were nonexistent or have minor discrepancies with the accessibility guidelines as stipulated in the said law. Findings from the interviews conducted revealed the factors that hindered the stores' full compliance with the Accessibility Law such as the limitations of renting the space, size of the store area, and budget for construction. Moreover, the results showed that PWDs, especially those with motion impairments, seldom go to the convenience stores. Nonetheless, the store managers and/or employees confirmed their awareness of the needs of PWDs. The researcher encourages interior design students and professionals to collaborate with other allied professions to study the country's public establishments with regard to the needs of PWDs. Likewise, the researcher recommends re-examining Batas Pambansa Bilang 344 and suggesting necessary design features for its improvement.
Thesis (BS Interior Design)--University of he Philippines Diliman.
Keywords: Convenience stores -- Philippines -- Barrier-free design